TINGKAT KEMAMPUAN DIGITALISASI KOMUNIKASI GURU DALAM MENYELESAIKAN BEBAN KERJA ADMINISTRASI DI SMP NEGERI 1 PEGAJAHAN - Ibrahim, Dimas; Harahap, Nursapia (Asosiasi Ide Bahasa Kepri, 2024)
This study aims to determine the level of communication digitization ability of teachers in completing administrative workload at SMP Negeri 1 Pegajahan. The research method used was qualitative with a case study approach. Data collection techniques were applied through in-depth interviews with 10 teachers and participant observation at SMP Negeri 1 Pegajahan. The results showed that the level of communication digitization ability of teachers at SMP Negeri 1 Pegajahan was still relatively low. This can be seen from the fact that many teachers still apply manual methods in completing administrative workloads, such as using paper and pens to write reports and correspondence. In addition, teachers are also still not accustomed to using digital applications to communicate with parents and guardians. Based on the results of the study, it can be concluded that it is necessary to improve the digitalization communication skills of teachers at SMP Negeri 1 Pegajahan. This can be done through training and workshops on the use of digital applications for administration and communication. In addition, schools also need to provide adequate infrastructure, such as computers and the internet, so that teachers can easily use digital applications.